Hipertermia Maligna: Tinjauan Pustaka: Tinjauan Pustaka - Pandrya, Carla Oktaviani; Anderson Surya, Kevin (Cermin Dunia Kedokteran, 2026)
Malignant hyperthermia (MH) is a life-threatening syndrome triggered by inhaled anesthetics and depolarizing muscle relaxants like succinylcholine, leading to uncontrolled skeletal muscle hypermetabolism. This condition is marked by massive calcium release from the endoplasmic reticulum, causing muscle rigidity, increased temperature, and metabolic disturbances. The genetic basis of MH is linked to mutations in the CACNA1S gene, which encodes a subunit of the dihydropyridine receptor (DHPR), which is essential to muscle calcium regulation. The condition is often triggered during surgeries requiring general or regional anesthesia, particularly in individuals with a family history of MH. Clinical manifestations may include hypercapnia, tachycardia, acidosis, rhabdomyolysis, and multi-organ dysfunction. Early diagnosis remains challenging because MH may resemble other hypermetabolic conditions and can progress rapidly if left untreated. Treatment involves the administration of dantrolene, a post-synaptic muscle relaxant that reduces excitation-contraction coupling (ECC) and mitigates hypermetabolism. Early recognition and prompt dantrolene administration are vital for successful management.